1945
DOI: 10.1021/ja01225a061
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the Insecticidal Resin of the Yam Bean (Pachyrrhizus erosus)1

Abstract: The seeds of the yam bean show a toxicity to several species of insects comparable with that of the rotenone-bearing roots of Derris and Lonchocarpus.4 They are of interest as a potential source

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1948
1948
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…All compounds (1)(2)(3)(4)(5)(6)(7) were characterized by spectrometric methods (*H nmr, BC nmr, ir, and ms) and by comparison with the data in the literature. Not all spectral data have been reported hitherto and, therefore, a detailed spectrometric study was undertaken (including 360 MHz nmr and 20 MHz BC nmr). A comparison was made between some reported data from the literature and those found in this communication.…”
Section: (S)mentioning
confidence: 99%
See 2 more Smart Citations
“…All compounds (1)(2)(3)(4)(5)(6)(7) were characterized by spectrometric methods (*H nmr, BC nmr, ir, and ms) and by comparison with the data in the literature. Not all spectral data have been reported hitherto and, therefore, a detailed spectrometric study was undertaken (including 360 MHz nmr and 20 MHz BC nmr). A comparison was made between some reported data from the literature and those found in this communication.…”
Section: (S)mentioning
confidence: 99%
“…The petroleum ether total extract of N. mitis roots showed significant acaricidal properties that were attributed to the presence of 12a-hydroxyrotenone [7].Neorautanenia species are a widespread group of Fabaceae (Papilionaceae) plants of Central and South Africa and are known for their poisonous properties (1). These plants are used by the native population as fish poison (2-5) and insecticide (6,7), while in the traditional medicine of Central Africa they are used against syphilis (8) and the treatment of female frigidity.4 The possible use of some of these plants for killing bilharziacarrying fresh water snails of the genera Bulinus and Biophalaria has also been reported (9).Several chemical studies have been performed already on Neorautanenia species, among others N. ficifolia (3,14,15), N. edulis (2,4,12,16,18), N. pseudopachyrrhiza (10,11,13), N. amboensis (5,12,17,19), and the related Pachyrrhizus erosus (20)(21)(22). In the course of our investigation on medicinal plants from Rwanda (Central Africa) we investigated Neorautanenia mitis (A.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two sets of aromatic protons were also present for a 1,2,4-trisubstituted benzene [δ 7.06 (1H, d), 6.31 (1H, dd), and 6.23 (1H, d)] and a 1,2,4,5-tetrasubstituted benzene [δ 7.17 (1H, s) and 6.26 (1H, s)], respectively. The 13 .74 (1H, dd), 3.00 (1H, dd), 2.69 (1H, dd), 1.33 (3H, s), and 1.24 (3H, s)] were typical of a 3-hydroxy-2,2dimethyldihydropyran moiety. 26,27 The oxygen atom of the dihydropyran ring was assigned at C-3 due to the upfield shift of the H-4 proton singlet (δ 6.26).…”
mentioning
confidence: 99%
“…The seeds of this plant have long been used as insecticides and fish poisons in various tropical countries ( Hansberry and Lee 1943 ). Toxicity studies of yam bean seeds showed that it has a great value as botanical insecticides to some important insect pests ( Hansberry and Lee 1943 , Lee and Hansberry 1943 , Plank 1944 , Norton and Hansberry 1945 , Hansberry et al. 1947 , Chiu 1950 , Tangchitphinitkan et al.…”
mentioning
confidence: 99%